B Cell Reconstitution and Influencing Factors After Hematopoietic Stem Cell Transplantation in Children - van der Maas, Nicolaas G.; Berghuis, Dagmar; van der Burg, Mirjam; Lankester, Arjan C. (Frontiers in Immunology, 2019)
B cell reconstitution after hematopoietic stem cell transplantation (HSCT) is variable and influenced by different patient, donor and treatment related factors. In this review we describe B cell reconstitution after pediatric allogeneic HSCT including the kinetics of reconstitution of the different B cell subsets and the development of the B cell receptor (BCR) repertoire and discuss the influencing factors. Observational studies show important roles for stem cell source, conditioning regimen and graft versus host disease in B cell reconstitution. In addition, B cell recovery can play an important role in post-transplant infections and vaccine responses to encapsulated bacteria, such as pneumococcus. A substantial number of patients experience impaired B cell function and/or dependency on Ig substitution after allogeneic HSCT. The underlying mechanisms are largely unresolved. The integrated aspects of B cell recovery after HSCT, especially BCR repertoire reconstitution, are awaiting further investigation using modern techniques in order to gain more insight into B cell reconstitution and to develop strategies to improve humoral immunity after allogeneic HSCT.